Statistics of Medical Imaging A Chapman & Hall/CRC Interdisciplinary Statistics Series. A Chapman & Hall/CRC Interdisciplinary Statistics Series. Issue 3 (25th February 2013) - Lin, Teh
Abstract : Statistics of Medical Imaging, Lei Tianhu, CRC Press, Boca Raton, FL, 2011. 438 pp. Price: $99.95. ISBN 9781420088427 (hardcover).